Should teens be allowed to consent for vaccines? - John Lantos (Shalamar Medical & Dental College, Lahore, Pakistan, 2021)
Teens and children will need to be vaccinated in order to achieve herd immunity against COVID-19. Most parents are eager to have their teens immunized, whereas some are hesitant. Should teens be allowed to consent to immunization even if their parents' objects? Vaccines are safe and effective, medically recommended, and good for both the individual and the community. Inspite of these powerful arguments, the law lags behind. Most parents want their teens to be immunized. Most vaccine-hesitant parents ultimately agree to vaccination. Furthermore, teens who get COVID generally have mild cases. For now, the law in most states does not permit teens to consent to the COVID-19 vaccine without parental permission.